2021
DOI: 10.12659/msm.934588
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Clinicopathological Factors Influencing Overall Survival and Event-Free Survival of Patients with Cervical Cancer: A Systematic Review and Meta-Analysis

Abstract: Background Cervical cancer (CC) is the most frequent type of cancer among women and its poor prognosis is a main concern, while the prognostic factors for CC have still remained controversial. We conducted this systematic review and meta-analysis to identify the prognostic significance of clinicopathological factors, influencing overall survival (OS), and event-free survival (EFS) of CC patients. Material/Methods The electronic databases of PubMed, EmBase, and the Cochr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 166 publications
(35 reference statements)
0
3
2
Order By: Relevance
“…In the present study, we have also evaluated the prognostic value and relevance of clinicopathological parameters and combined treatment with the PET and CT ndings. Contrary to the ndings of a metaanalysis 29 , we found no signi cant differences in clinicopathological parameters even for risk factors that have a high impact on survival (such as adenocarcinoma and the presence of parametrial invasion extending to pelvic wall), perhaps due to the small number of patients in the present study. In terms of combined treatment, our results showed that combined brachytherapy or chemotherapy with radiotherapy improved PFS and/or OS, in agreement with previous studies 28, 30 .…”
Section: Discussioncontrasting
confidence: 99%
“…In the present study, we have also evaluated the prognostic value and relevance of clinicopathological parameters and combined treatment with the PET and CT ndings. Contrary to the ndings of a metaanalysis 29 , we found no signi cant differences in clinicopathological parameters even for risk factors that have a high impact on survival (such as adenocarcinoma and the presence of parametrial invasion extending to pelvic wall), perhaps due to the small number of patients in the present study. In terms of combined treatment, our results showed that combined brachytherapy or chemotherapy with radiotherapy improved PFS and/or OS, in agreement with previous studies 28, 30 .…”
Section: Discussioncontrasting
confidence: 99%
“…In the present study, we have also evaluated the prognostic value and relevance of clinicopathological parameters and combined treatment with the PET and CT findings. Contrary to the findings of a meta-analysis 29 , we found no significant differences in clinicopathological parameters even for risk factors that have a high impact on survival (such as adenocarcinoma and the presence of parametrial invasion extending to pelvic wall), perhaps due to the small number of patients in the present study. In terms of combined treatment, our results showed that combined brachytherapy or chemotherapy with radiotherapy improved PFS and/or OS, in agreement with previous studies 28 , 30 .…”
Section: Discussioncontrasting
confidence: 99%
“…This phenomenon is associated with systemic inflammation and an increase in WBC (Cho et al, 2016). Leukocytosis can be caused by the upregulated expression of hematological growth factors, including granulocyte colony-stimulating factor (G-CSF), granulocyte macrophage colony-stimulating factor (GM-CSF), interleukin (IL)-1, IL-6, or tumor necrosis factor (TNF)-α, which are associated with leukemoid reactions (Kang et al, 2022; Madeddu et al, 2022). Hematological growth factors stimulate WBC differentiation for a defensive response.…”
Section: Discussionmentioning
confidence: 99%